Subcutaneous Zygomycosis Due to Basidiobolus ranarum: A Case Report from Maharastra, India - Mani Anand; Sanjay D. Deshmukh; Dilip P. Pande; Suresh Naik; Dhyaneshwari P. Ghadage (Journal of Tropical Medicine)
Entomophthoromycosis is a rare entity. We hereby report a case of entomophthoromycosis in a three-year-old Asian child who presented with a painless, nontender, rapidly increasing large swelling on the thigh of six months duration, which was initially misdiagnosed as a soft tissue tumor and resected. The cause of misleading diagnosis was rapid growth of the lesion in a short duration of time, indicating the possibility of a tumor. Histopathological examination revealed an inflammatory lesion with aseptate fungal hyphae and the characteristic Splendore-Hoeppli phenomenon. Microbiological examination identified the fungus as Basidiobolus ranarum. Complete excision of the lesion followed by antifungal therapy was associated with complete recovery. Entomophthoromycosis should be considered early when children from endemic areas present with unusual, rapid-growing lesions of the subcutaneous region. In order to emphasize tumor-like presentation of zygomycosis, we are presenting this case.